Enhancing EFL students’ engagement in online synchronous classes: The role of the Mentimeter platform - Tarazi, Ayat; Ortega-Martín, José Luis (Frontiers in Psychology, 2023)
The present research aimed to evaluate teachers’ attitudes toward the use of the Mentimeter platform in synchronous education. This study also sought to delve into teachers’ perspectives on the role of the Mentimeter platform in improving students’ engagement in online synchronous classes. In doing so, a total of 44 Palestinian teachers were asked to respond to the closed-ended questionnaires. The study’s outcomes demonstrated that teachers had positive attitudes toward employing the Mentimeter platform in synchronous education. The results also indicated that almost all educators perceived that the Mentimeter platform serves a vital role in increasing student engagement in online synchronous sessions. Teachers asserted that Mentimeter presentation styles decrease the probability of boredom among students, which in turn encourages them to actively participate in online synchronous environments. The limitations and implications of the current investigation are thoroughly discussed.